2013
DOI: 10.1353/cpr.2013.0033
|View full text |Cite
|
Sign up to set email alerts
|

Using the Delphi and Snow Card Techniques to Build Consensus Among Diverse Community and Academic Stakeholders

Abstract: BACKGROUND The New York University- New York City Health and Hospitals Corporation (NYU-HHC) Clinical and Translational Science Institute (CTSI) used a community-based participatory research (CBPR) and consensus-building approach among its community advisory board (CAB) and steering committee (SC) members to formulate research priorities to foster shared research collaborations. METHODS The Delphi technique is a methodology used to generate consensus from diverse perspectives and organizational agendas throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Articles in which several different data collection activities were identified to engage patients were reviewed, such as through surveys and key informant interviews [ 44 – 51 ], focus groups [ 13 , 14 , 52 66 ], and patient panels [ 67 ]. While data collection activities differed, a common approach across Tier 2 included a two-step process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles in which several different data collection activities were identified to engage patients were reviewed, such as through surveys and key informant interviews [ 44 – 51 ], focus groups [ 13 , 14 , 52 66 ], and patient panels [ 67 ]. While data collection activities differed, a common approach across Tier 2 included a two-step process.…”
Section: Resultsmentioning
confidence: 99%
“…Most often, success was not reliant on clear evaluation metrics but on the authors’ reviews of the process [ 56 ] or on opinions formed in reaching objectives that were not explicitly stated a priori [ 14 , 56 ]. For example, Rideout et al [ 52 ] identified that engaging patients at the macro level provided ample opportunity for shared research collaboration related to CVD and mental health. Working groups were formed with leadership provided by co-chairs: one from specific content areas and one from the public/community leaders.…”
Section: Resultsmentioning
confidence: 99%
“…However, conducting CBPR requires building the capacity of both community stakeholders and academic researchers (Crosby et al 2013;Goytia et al 2013;Kwon et al 2012). Though several CBPR engagement and training models have been published (Allen et al 2013;Baquet et al 2013;Cole et al 2013;Crosby et al 2013;Goytia et al 2013;Healey, Reed & Huber 2013;Martin del Campo et al 2013;Rideout et al 2013;Smith, Kaufman & Dearlove 2013;Young-Lorion et al 2013), few have focused on work with Pacific Islander communities (DiStefano et al 2013;Kaholokula et al 2014;Kwan et al 2012Kwan et al , 2014Palmer 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi technique has been a popular method for developing indicators reflecting patient and general practitioner perspectives of chronic illness, performance indicators for emergency medicine, and indicators for cardiovascular disease (6,8,(16)(17)(18)(19). Delphi methodology succeeds in converging agreement, not in ensuring the validity of the results.…”
Section: Modified Delphi Techniquementioning
confidence: 99%